Immigrant children education as means of integration: the Lithuanian case - Orechova, Monika (Journal of Education Culture and Society, 2018)
Aim. This research paper discusses the educational process of immigrant children in Lithuania with the intention to determine the integration trajectory most likely to be chosen by the immigrant students. Methods. The research methods include legal analysis of Lithuanian legislations related to immigration, immigrant integration and education, meta-analysis of previous research on immigrant integration into Lithuanian society as well as semi-structured interviews with experts of the field. Results. Having completed the research, the following conclusion has been drawn: immigrant children education in Lithuania does not tend to create conditions for successful integration and more often than not influences immigrant students to choose those integration paths that may inspire inner or outer conflict. This is due to the lack of integration policy and strategy at the state level as well as the tendency to create a cultural hierarchy wherein the Lithuanian culture is implicitly considered as above others. Practical application. The results of the research can be used to improve the conditions of immigrant children education in Lithuanian schools on the national level as well as by schools willing to foster the integration of immigrant students; the results can also be considered in the process of establishing integration policy on the state level.